The unresolved National Question in South Africa : left thought under apartheid and beyond - Webster, Eddie; Pampallis, Karin (Wits University Press, 2017)
The re-emergence of debates on the decolonisation of knowledge has revived interest in the National Question, which began over a century ago and remains unresolved. Tensions that were suppressed and hidden in the past are now being openly debated. Despite this, the goal of one united nation living prosperously under a constitutional democracy remains elusive. This volume examines the way in which various strands of left thought have addressed the National Question, especially during the apartheid years, and goes on to discuss its relevance for South Africa today and in the future. Contributors have defined the question as they believe appropriate, which has resulted in a rich tapestry of interweaving perceptions about the unresolved National Question. The volume is structured in two parts. The first examines four foundational traditions - Marxism-Leninism (the Colonialism of a Special Type thesis); the Congress tradition; the Trotskyist tradition; and Africanism. The second part explores the various shifts in the debate from the 1960s onwards, and includes chapters on Afrikaner nationalism, ethnic issues, Black Consciousness, feminism, workerism and constitutionalism. By revisiting these debates, the volume will become a catalyst for an enriched debate on our identity and our future.